Lifetime Musical Activities and Cognitive Function of the Elderly - Nevriana, Alicia; Riono, Pandu; Rahardjo, Tri Budi W.; Kusumadjati, Adji (UI Scholars Hub, 2013)
Penurunan fungsi kognitif merupakan salah satu masalah umum pada lanjut usia yang mampu memengaruhi kualitas hidup mereka. Musik merupakan sebuah elemen yang dipercaya mampu berkontribusi terhadap kualitas hidup mereka. Meski demikian, hubungan antara aktivitas musikal yang dilakukan sepanjang hidup dan fungsi kognitif lansia belum diketahui secara pasti. Pada penelitian ini, hubungan antara aktivitas musikal sepanjang hidup dan fungsi kognitif dievaluasi. Lima puluh tiga lansia penghuni panti tresna werdha di Jakarta Timur dipilih dan diwawancarai terkait karakteristik dan aktivitas musikal sepanjang hidup mereka. Fungsi kognitif juga diukur menggunakan MMSE. Hasil penelitian ini menunjukkan adanya kemungkinan asosiasi antara aktivitas musikal sepanjang hidup dan fungsi kognitif lansia. Hasil penelitian juga menunjukkan bahwa partisipan yang tidak aktif melakukan aktivitas musikal sepanjang hidupnya dua kali lebih berpeluang untuk mengalami gangguan fungsi kognitif dibandingkan dengan mereka yang aktif melakukan aktivitas musikal, setelah disesuaikan dengan karakteristiknya. Hasil korelasi ini mengisyaratkan pengaruh bermanfaat dari aktivitas musikal sepanjang hidup terhadap fungsi kognitif lansia. Decreasing cognitive function of the elderly is one of the most common problems that might affect their quality of life. Music is an element that is believed to be able to contribute to the quality of life of the elderly. However, whether musical activities that are done throughout the life span related to cognitive function is unclear. In this research, we evaluated the association between lifetime musical activities and cognitive function. Fifty three older adults from three nursing homes in East Jakarta were selected and interviewed regarding their characteristics and lifetime musical activities. Cognitive function was also measured using Mini Mental State Examinaion (MMSE). The results of this preliminary study revealed that a possibility of an association between lifetime musical activities and cognitive function of the elderly was indicated. The result also showed that the participants who were not actively involved in musical activities during their lifetime were twice more likely to develop cognitive function impairment than the elderly who were actively involved in musical activities, after being adjusted by the characteristics. These correlational results suggest the beneficial effect of musical activities throughout the life span on cognitive functioning for the elderly.